The release of exosomes in the medial prefrontal cortex and nucleus accumbens brain regions of chronic constriction injury (CCI) model mice could elevate the pain sensation. (1st April 2020) - Yu, Xiaolu; Abdul, Mannan; Fan, Bing-Qian; Zhang, Lilu; Lin, Xing; Wu, Yan; Fu, Hui; Lin, Qisi; Meng, Hao
Abstract: Background: Brain function relies on the capacity of neurons to locally modulate each other at the level of synapses. Therefore, the exosomal pathway may constitute a well-designed mechanism for local and systemic interneuronal transfer of information within functional brain networks. Exosomes bind to and are endocytosed by neurons of different brain regions to play a definite role. The medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) brain regions are known to involve in pain modulation. Our study observes the roles of exosomal activity in these two dominant regions of the pain-related pathway, and there influence on the analgesic effects in CCI mice. Methods: We induced pain exosomes in the mPFC and NAc in the mice of chronic constriction injury of the sciatic nerve model to produce neuropathic pain, and assessed changes that might affect analgesic behaviors. These changes were measured through a combination of behavioral, surgical, and other cellular testings. Results: Our study found that pain expression was elevated in mice given exogenous exosomes isolated from CCI mice, especially at the 2 h and 4 h time interval, in mice given exosomes at the mPFC and NAc, respectively. We also found that inhibiting formation of pain exosomes through GW4869 within the mPFC and NAc can elevate the pain threshold. Conclusion: Results from our study supported the idea that the release of mPFC and NAc exosomes of CCI model has elevated the pain sensations in the subjected mice. This study will further help in designing new clinical trials, and will revolutionize the drug-induced anesthetic responses.